2005
DOI: 10.1080/01485010590919701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Weight on Sperm Concentration in Normozoospermic Males

Abstract: & A total of 274 men (aged: 26 AE 4.9 years) with normozoospermia were enrolled into this study. Their body mass index (BMI: kg=m 2 ) varied between 17 and 39. According to BMI, the patients were divided into four groups: Group 1: 17-20, Group 2: 20.1-25, Group 3: 25.1-30 and Group 4: 30.1-39. Twenty-nine subjects were found in the first, 96 in the second, 91 in the third and 58 men in the fourth group. Sperm concentration was significantly lower in the obese group (29 Â 10 6 =ml, p < 0.05) than in the group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 10 publications
(10 reference statements)
4
35
1
3
Order By: Relevance
“…This results in agreement with previous studies [9][10][11][12][13][14].A possible association between metabolic syndrome (MS) and male infertility has been hypothesized. Male obesity and (MS) are associated with hypogonadism [27].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This results in agreement with previous studies [9][10][11][12][13][14].A possible association between metabolic syndrome (MS) and male infertility has been hypothesized. Male obesity and (MS) are associated with hypogonadism [27].…”
Section: Discussionsupporting
confidence: 83%
“…Total body fat, intra-abdominal fat, and subcutaneous fat have all been associated with low levels of total and free testosterone [8]. Body mass index has been associated with alterations in sperm parameters in several reports [9][10][11]. Many studies have…”
Section: Introductionmentioning
confidence: 99%
“…There is a negative impact of male obesity on standard semen parameters, including motility, count, and hormone abundance, such as testosterone and inhibin B (1,5,16,18,21,22,32,35,37,45,47,52,62,69,85). Further studies have reported reduced pregnancy success and live birth outcomes after IVF treatment in overweight and obese men (9, 42).…”
mentioning
confidence: 99%
“…Consequently, the rates of male obesity in reproductive age men has nearly tripled since the 1970s (33). Recent studies in both humans and other species shows that male obesity impairs male reproductive potential, affecting both the molecular and physical structure of sperm (1,10,16,20,21,34,35,38,45,47,50,63,75,79) and the health of the developing fetus and subsequent offspring (9,24,42,55,59). …”
mentioning
confidence: 99%
“…In a follow up study in couples enrolled in the agricultural health study in USA [23] found a dose-response relationship between infertility and male BMI and that association was similar for older or younger men. Other authors have found that semen parameters are affected in men BMI above or below normal levels [24][25][26][27][28][29] . Maternal BMI may also have effect on the semen quality in sons of overweight mothers.…”
Section: Obesitymentioning
confidence: 99%